Survival Outcomes of Local Compared With Systemic First Treatment of Non-Small Cell Lung Cancer Brain Metastases - Liu, Hong-Mei; Meng, Chun-Liu; Zhao, Lu-Jun (Frontiers in Oncology, 2021)
Abstract Objective: This retrospective study evaluated the survival advantage of local treatment targeted to brain metastases, relative to systemic therapy, as the first option for brain metastases of non-small cell lung cancer (NSCLC). Methods: First reviewed were 291 cases of NSCLC brain metastases from 2 centers. All patients were at least 18 years old, with histologically confirmed NSCLC, and required and underwent both local (radiotherapy or brain surgery) and systemic treatment (chemotherapy and tyrosine kinase inhibitor [TKI] medication). Demographics, clinical characteristics, and treatment-related variables were collected. Results: The final population comprised 160 patients. Overall, the multivariate analysis suggested that the following were associated with better survival: >3 cycles of chemotherapy; stereotactic radiosurgery; and TKI medication (all, P = 0.000). Local treatment that began within 1 week of the diagnosis of brain metastases was associated with poorer survival (P = 0.006). Among the 111 patients with symptomatic brain metastases, the multivariate analysis indicated that better survival was associated with >3 cycles of chemotherapy (P = 0.000), radiation dose >40 Gy (P = 0.001), stereotactic radiosurgery (P = 0.000), and TKI medication (P = 0.000); while local treatment that began within 1 week after the diagnosis of brain metastases was associated with poorer survival (P = 0.015). Conclusions: For patients with NSCLC brain metastases, regardless of the presence of clinical symptoms associated with brain metastases, systemic treatment before local may be better for survival. Even when used to relieve clinical symptoms, local treatment should be within a setting of sufficient systemic treatment.